Hemodynamic Efficacy of Flow Diverter Stents in Intracranial Aneurysms: A Computational Analysis of Wall Shear Stress - Arafat, Muhammad Affiq Syukri; Nor Salim, Nor Adrian; Nur Amani Hanis Roseman (Journal of Advanced Mechanical Engineering Applications, 2026)
Intracranial aneurysms (IAs) pose a severe clinical risk of catastrophic rupture, a life-threatening event largely driven by continuous and localized hemodynamic forces acting upon the structurally weakened arterial wall. While the deployment of flow diverter (FD) stents has emerged as a highly effective endovascular intervention to disrupt intra-aneurysmal flow, determining the most mechanically protective stent configuration remains a significant challenge. Suboptimal deployment can inadvertently worsen local shear stresses, exacerbate endothelial dysfunction and accelerate vascular degradation. Therefore, this study aims to evaluate the hemodynamic efficacy of various FD stent configurations by analyzing their impact on Time-Averaged Wall Shear Stress (TAWSS) distributions—specifically physiological , stagnated , and critical  shear regions to identify designs that best mitigate rupture risks. Computational hemodynamic analysis revealed varying degrees of efficacy across the tested configurations. A hemodynamically ideal stent must promote  to maintain endothelial homeostasis, while strictly minimizing, which triggers inflammatory pathways, and  (> 10 Pa), which drives destructive extracellular matrix degradation via matrix metalloproteinases (MMPs). Among the evaluated designs, Model 5 demonstrated the most optimal and highly protective mechanical profile. It successfully suppressed the  luminal coverage area to merely 0.361%, effectively dampening the incoming high-velocity blood jets and balancing the overall shear distribution far better than the untreated baseline and other configurations. These findings emphasize that selecting the optimal FD stent geometry is crucial for restoring physiological hemodynamics and preventing post-treatment hemorrhagic rupture, providing essential insights for future neurovascular stent designs.